2023
DOI: 10.1111/joes.12550
|View full text |Cite
|
Sign up to set email alerts
|

Central bank communication and social media: From silence to Twitter

Abstract: This paper discusses the evolution of central bank communication, focusing on recent efforts by central banks to engage with a wider audience via social media. We document the social media presence of major central banks and discuss how analyzing Twitter content by and about monetary policy makers can inform about the effectiveness of communication in influencing beliefs. We focus on recent techniques employed in analyzing social media content in order to understand how central bank communication affects expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 134 publications
0
3
0
Order By: Relevance
“…Second, we find that Twitter is the most robust proxy of investor attention and provides additional information compared to indicators derived from Google Trends or the media. We thus contribute to the emerging literature on the use of social media by central banks and on its ability to communicate effectively with the public (Ehrmann and Wabitsch, 2022;Masciandaro et al, 2022) by showing that Twitter is not just noisy but reflects the perceptions of the general public and investors about the central bank's actions. 3 Last, while investor attention has predictive power for the magnitude of the price (yield) changes, we do not find any forecasting power on (non-absolute) market returns, even when we combine our investor attention proxy with a measure of investor sentiment before the news.…”
Section: Introductionmentioning
confidence: 89%
“…Second, we find that Twitter is the most robust proxy of investor attention and provides additional information compared to indicators derived from Google Trends or the media. We thus contribute to the emerging literature on the use of social media by central banks and on its ability to communicate effectively with the public (Ehrmann and Wabitsch, 2022;Masciandaro et al, 2022) by showing that Twitter is not just noisy but reflects the perceptions of the general public and investors about the central bank's actions. 3 Last, while investor attention has predictive power for the magnitude of the price (yield) changes, we do not find any forecasting power on (non-absolute) market returns, even when we combine our investor attention proxy with a measure of investor sentiment before the news.…”
Section: Introductionmentioning
confidence: 89%
“…Investigating the application of foundational communication theories and the advancement of social metric integration could alleviate some of the identified challenges associated with the integration effort; research by Manca et al [18] showed that students primarily used platforms such as Instagram, Pinterest, Snapchat, and WhatsApp for content creation and engaging in discussions with peers for educational and assessment purposes. The role of social media in education has attracted increasing attention from scholars [11,19], with various studies demonstrating its use by educators for personal, professional, and pedagogical goals [20]. Notably, research has underscored the value of Facebook groups in improving educational experiences, offering benefits not found in traditional online Learning Management Systems [21].…”
Section: Introductionmentioning
confidence: 99%
“…If previously in the 1990s, Blinder (2008) said that communications conveyed by the Central Bank relating to monetary policy were only surrounded by silence and secrecy, in the last few decades, communications carried out by the Central Bank have undergone transformation or change in the form of communication transparency, where communication delivered by the central bank has become a key instrument in the central bank's policy tools and has drastically changed the way monetary policy is carried out (Masciandaro et al, 2023).…”
Section: Introductionmentioning
confidence: 99%